Political Communication and Legal Populism in Contemporary Indonesian Governance : The Transformation of Public Trust in State Institutions - Joni Laksito (Universitas Sains dan Teknologi Komputer, 2026)
The transformation of political communication in the digital democratic era has reshaped how governments build legitimacy and maintain public trust in state institutions. Although the literature on legal populism and institutional trust has expanded considerably, limited attention has been paid to how political communication mediates the relationship between law, legitimacy, and public trust. This study examines the role of political communication in constructing institutional legitimacy through legal populism within the context of contemporary Indonesian governance. Employing a qualitative approach, the study utilizes political discourse analysis of 245 documents, including presidential speeches, government press releases, ministerial statements, strategic policy documents, official government social media content, and national media coverage published between 2019 and 2025. Data were analyzed using NVivo 14 through thematic coding and inter-narrative relationship analysis. The findings reveal that governmental political communication is structured around four interconnected dimensions: the construction of the people as the primary source of legitimacy, legal legitimacy as a mechanism for policy justification, national interest narratives as a developmental framework, and the representation of state institutions as guardians of public interests. The interaction of these dimensions contributes to the formation of public trust, which subsequently reinforces institutional legitimacy and governance stability. This study develops the concept of **Communicative Legal Populism**, defined as a political legitimation mechanism that integrates law, political communication, national interests, and popular representation in the construction of public trust. The findings extend the literature on legal populism and institutional trust by demonstrating that political communication functions as a critical mediator between law and state legitimacy in contemporary democracies.